2012
DOI: 10.1108/03074351211266801
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of distress and identification of potential M&As targets in UK

Abstract: Purpose -This study seeks to identify financial characteristics that can be employed to assess and predict corporate financial distress in publicly traded firms quoted in the London Stock Exchange. Design/Methodology/Approach -The model incorporates three existing literatures as an alternative to bankruptcy. The model has two stages: the first stage discriminates financially healthy or distressed firms utilizing Binary Logit Regression while in the second stage with the use of the univariate analysis, firms ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The results showed that both profitability ratios were negatively significant in predicting financial distress. These results were in accordance with studies by Ong et al (2011), Juniarti (2013, Polemis and Gounopoulos (2012) and Thai et al (2014). Furthermore, these results imply that a high ability to generate profit will help a firm to reduce its financial distress risk.…”
Section: Results and Analysissupporting
confidence: 93%
“…The results showed that both profitability ratios were negatively significant in predicting financial distress. These results were in accordance with studies by Ong et al (2011), Juniarti (2013, Polemis and Gounopoulos (2012) and Thai et al (2014). Furthermore, these results imply that a high ability to generate profit will help a firm to reduce its financial distress risk.…”
Section: Results and Analysissupporting
confidence: 93%
“…Bankruptcy prediction is among the most well researched topics in the finance and strategic management literature (Polemis & Gounopoulos, 2012). The early researchers (Ramser & Foster, 1931;Fitzpatrick, 1932;Winakor & Smith, 1935;Merwin, 1942) focused on the comparison of the values of financial ratios in bankrupt and non-bankrupt companies and concluded that the ratios of the bankrupt companies were poorer (Ugurlu & Aksoy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of takeover intentions, we consider the operational profit (earnings before interest and taxation) because it estimates how efficiently a company can earn profit from its assets, regardless of its size and without being affected by management financial decisions. A high value of this indicator can provide a sign of solid operational performance (Polemis and Gounopoulos 2012;Purba and Septian 2019). In the case of obtaining financial gains, the performance expressed through profit and loss is relevant as an overall result of the activity in an accounting period (Glendening et al 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…For the second objective, we explored the relationship between the purchased stake in minority acquisitions and the efficiency of the operational activity, reflected by earnings before interest and taxes (henceforth, EBIT), as stated by Polemis and Gounopoulos (2012) and Purba and Septian (2019). Since the distribution of purchased stake is bimodal, clearly showing different distributions for the high values (between 1 and 50%) and for the low values of stake (up to 1%), we used a quantile regression (QR) approach, specifically the conditional quantile regression estimator developed by Koenker and Hallock (2001).…”
Section: Variable Description and Proposed Modelsmentioning
confidence: 99%